2020
DOI: 10.1093/eurpub/ckaa165.841
|View full text |Cite
|
Sign up to set email alerts
|

The importance and challenge of carcinogenic air pollutants for health risk and impact assessment

Abstract: Along the years, the International Agency for Research on Cancer (IARC) has classified many air pollutants components as carcinogens, including solvents, diesel engine exhaust, metals, such as chromium, nickel, arsenic, and cadmium. The IARC list of Group 1 carcinogens includes benzene, diesel exhaust, benzo[a]pyrene (B[a]P, a polycyclic aromatic hydrocarbon [PAH]), indoor emissions from coal combustion, and 1,3-buta-diene. Sources, mainly combustion-related, that emit airborne carcinogens can be both in indoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In Spain, Garcıá-Perez et al reported ALL excess risk in children living in urban areas (OR = 1.36; 95% CI 1.02-1.80) (54) and excess risk of ALL in children living within a 2.5-km radius from sources emitting pollutants (OR = 1.31; 95% CI 1.03-1.67) (54, 55). Sources of stationary and mobile polluting sources may include service stations, incinerators, industrial facilities, crematories, urban landfills, artisanal brick kilns, vehicles, and areas burning biomass as fuel (56). These sources emit benzene, PAHs, and PM 2.5 into the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…In Spain, Garcıá-Perez et al reported ALL excess risk in children living in urban areas (OR = 1.36; 95% CI 1.02-1.80) (54) and excess risk of ALL in children living within a 2.5-km radius from sources emitting pollutants (OR = 1.31; 95% CI 1.03-1.67) (54, 55). Sources of stationary and mobile polluting sources may include service stations, incinerators, industrial facilities, crematories, urban landfills, artisanal brick kilns, vehicles, and areas burning biomass as fuel (56). These sources emit benzene, PAHs, and PM 2.5 into the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Aerosols, present in atmosphere play a major role as air pollutants, and their presence can lead to various climatological shifts and health consequences [1]. During wintertime and spring, dense haze and dust storms have had a significant impact on millions of individuals in the South Asian region [2,3].…”
Section: Introductionmentioning
confidence: 99%